2014
DOI: 10.1007/s10495-014-0971-6
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin induces apoptosis by targeting inhibitor of apoptosis proteins and Ku70–Bax interaction in prostate cancer

Abstract: Dysfunction of the apoptotic pathway in prostate cancer cells confers apoptosis resistance towards various therapies. A novel strategy to overcome resistance is to directly target the apoptotic pathway in cancer cells. Apigenin, an anticancer agent, selectively toxic to cancer cells induces cell cycle arrest and apoptosis through mechanisms which are not fully explored. In the present study we provide novel insight into the mechanisms of apoptosis induction by apigenin. Treatment of androgen-refractory human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 44 publications
2
73
0
2
Order By: Relevance
“…This treatment induced apoptosis through downregulation of Bcl-2, upregulation of Apaf-1, p21/Waf1 and p53 expression, and inhibition of PI3K/Akt and NF-κB signaling pathways [136]. Shukla et al [137] demonstrated the ability of apigenin in inhibiting the IAP family of proteins, thereby making prostate cancer cells more susceptible to Bax-mediated apoptosis. Apigenin treatment to prostate cancer cells caused decrease in HDAC1 thereby altering acetylation status, resulting in increased acetylation of the lysine residues of Ku70, thereby releasing Bax from the complex facilitating apoptosis [137].…”
Section: Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment induced apoptosis through downregulation of Bcl-2, upregulation of Apaf-1, p21/Waf1 and p53 expression, and inhibition of PI3K/Akt and NF-κB signaling pathways [136]. Shukla et al [137] demonstrated the ability of apigenin in inhibiting the IAP family of proteins, thereby making prostate cancer cells more susceptible to Bax-mediated apoptosis. Apigenin treatment to prostate cancer cells caused decrease in HDAC1 thereby altering acetylation status, resulting in increased acetylation of the lysine residues of Ku70, thereby releasing Bax from the complex facilitating apoptosis [137].…”
Section: Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…Shukla et al [137] demonstrated the ability of apigenin in inhibiting the IAP family of proteins, thereby making prostate cancer cells more susceptible to Bax-mediated apoptosis. Apigenin treatment to prostate cancer cells caused decrease in HDAC1 thereby altering acetylation status, resulting in increased acetylation of the lysine residues of Ku70, thereby releasing Bax from the complex facilitating apoptosis [137]. In further studies of apigenin-mediated apoptosis in prostate cancer cells, Sharma et al [138] demonstrate preferential uptake and accumulation of apigenin in the nuclear matrix, binding it with the DNA to reduce oxidative DNA damage and apoptosis in prostate epithelial cells.…”
Section: Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…However, numerous in vivo studies revealed that apigenin showed ideal bioactivities in animal models given oral administration. Shukla, Fu, and Gupta (2014) reported that apigenin inhibited human prostate cancer cell line PC-3 proliferation with 40 µM IC50 value in vitro and suppressed prostate tumour growth in PC-3-derived xenograft nude mice model given 50 µg/mouse apigenin oral administration every day, whose doses are comparable to the daily consumption of flavonoid in humans. Wu et al (2014) proved that apigenin (30 mg/kg) oral administration inhibited pancreatic cancer tumour growth in xenograft nude mice model implanted with human pancreatic cancer cell line AsPc-1, on which apigenin showed anti-proliferative effect with an IC50 value of 28.5 µM in vitro.…”
Section: Apigenin Induces Ros Accumulation In Pancreatic Cancer Cellsmentioning
confidence: 99%
“…Localized prostate cancer is eminently treatable; however, no curative therapy is available once the cancer becomes invasive and metastasizes. 3,4 Therefore, identifying the role of new molecules of diagnostic and therapeutic significance remains a major focus of current cancer research.…”
Section: Introductionmentioning
confidence: 99%